Information technology law : the law and society - Murray, Andrew, 1972- (Oxford : Oxford University Press, 2013)
'Information Technology Law is the ideal companion for a course of study on IT law and the ways in which it is evolving in response to rapid technological and social change. This ground-breaking new work is the first textbook to systematically examine how the law and legal process of the UK interacts with the modern'information society' and the fast-moving process of digitization. It examines the challenges that this fast pace of change brings to the established legal order, which was developed to meet the needs of a traditional physical society. To address these issues, this book begins by defining the information society and discussing how it may be regulated. From there it moves to questions of internet governance and rights and responsibilities in the digital environment. Particular attention is paid to key regulatory'pressure points', including: DT copyright for digital products DT identity fraud DT electronic commerce DT privacy and surveillance Possible future challenges and opportunities are outlined and discussed, including e-government, virtual environments and property, and the development of web 3.0. Information Technology Law: The law and society covers all aspects of a course of study on IT law, and is therefore an ideal text for students. The author's highly original and thought-provoking approach to the subject also makes it essential reading for researchers, IT professionals and policymakers. Online Resource Centre This book is accompanied by an Online Resource Centre containing the following resources for students: DT Regular podcast updates from the author DT A selection of useful web links DT A glossary of key terms DT A link to the author's IT law blog'--
The world of bits -- The network of networks -- Digitisation and society -- Regulating the digital environment -- Digital ownership -- Cyber-speech -- Social networking and antisocial conduct -- Defamation -- Intellectual property rights and the information society -- Software -- Copyright in the digital environment -- Databases -- Computer misuse -- Pornography and obscenity in the information society -- Crime and law enforcement in the information society -- Branding and and trade marks in the information society -- Electronic contracts -- Electronic payments -- Data protection -- Data and personal privacy -- The digital public sphere -- What way next?.
Includes bibliographical references and index.
Keywords: Computers -- Law and legislation -- United Kingdom; Internet -- Law and legislation -- United Kingdom; Copyright -- Computer programs -- United Kingdom; Information networks -- Law and legislation -- United Kingdom; Electronic contracts -- United Kingdom; Digital signatures -- Law and legislation -- United Kingdom; Data protection -- Law and legislation -- United Kingdom; Cyberspace -- United Kingdom